Communities being well for family well-being: Exploring the socio-ecological determinants of well-being in an Inuit community of Northern Quebec. (February 2018) - Fraser, Sarah L.; Parent, Valérie; Dupéré, Véronique
Inuit communities of Canada experience many disparities in health and psychosocial context. Research in community psychology has shown associations between such socio-ecological factors and individual well-being. The objective of the study was to explore how community-level determinants of well-being influence family well-being in a northern community of Nunavik, Quebec. A total of 14 participants were interviewed. A thematic inductive analysis was conducted to extract community determinants of family well-being from the data. A system science approach was used to explore the associations between determinants and larger psychosocial dynamics. A community workshop was held to discuss the results and their meaning. A total of 25 determinants were coded, 16 of which were community-level. Community-level stressors were highly interrelated, whereas community supports were generally disconnected and superimposed on narratives of stressors. Participants spoke of desired supports. In their narratives, these supports were connected to a variety of determinants of well-being, suggesting the need to connect, redefine and support existing resources rather than simply add on new ones. We discuss intricate links between family and community well-being in small and geographically isolated communities.